2021
DOI: 10.21203/rs.3.rs-133655/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential clinical utility of MUC5B und TOLLIP single nucleotide polymorphisms (SNPs) in the management of patients with IPF

Abstract: Background: Genetic variants of TOLLIP and MUC5B, both on chromosome 11, have been reported to be associated with the development and/or prognosis of idiopathic pulmonary fibrosis (IPF). This retrospective study was conducted to investigate the association of MUC5B and TOLLIP SNPs with disease outcome in IPF. 62 IPF patients and 50 healthy controls (HC) from our Institution were genotyped for SNPs within MUC5B (rs35705950) and TOLLIP (rs3750920 and rs5743890). Correlation of SNPs genotypes with survival, acute… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In addition, our data from a single registry should be verified with an independent group of IPF patients of different ethnicities. Despite these limitations, our exploratory study on a similarly sized group of patients as another IPF pharmacogenomic studies 5,32,33 demonstrated an association between the profibrotic variant and antifibrotic treatment outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, our data from a single registry should be verified with an independent group of IPF patients of different ethnicities. Despite these limitations, our exploratory study on a similarly sized group of patients as another IPF pharmacogenomic studies 5,32,33 demonstrated an association between the profibrotic variant and antifibrotic treatment outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…32 Other recent study investigated 62 IPF patients on antifibrotic treatment for MUC5B rs35705950 and TOLLIP rs5743890 polymorphisms. 33 This study reported that minor allele C in TOLLIP, an inhibitor of the toll-like receptors (TLRs) 2 and 4, but not MUC5B, was associated with worse survival, acute exacerbation and disease progression. 33 Similarly, in our cohort no association of MUC5B rs35705950 with acute exacerbation IPF nor radiological findings were observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to GWAS, some clinical retrospective studies have also demonstrated the function of TOLLIP in IPF. A retrospective study demonstrated that the minor allele (C) in TOLLIP rs5743890 was associated with worse survival and disease progression in patients with IPF [33]. In a post-hoc exploratory analysis of patients enrolled in the clinical trial "Evaluating the Effectiveness of Prednisone, Azathioprine, and N-Acetylcysteine in Patients with Idiopathic Pulmonary Fibrosis", a signi cant correlation was observed between the response to N-acetylcysteine (NAC) therapy and rs3750920 of TOLLIP [34].…”
Section: Discussionmentioning
confidence: 99%